Characterization of Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) young nests in a fragment of the Neotropical Forest - Camargo, Roberto da Silva [UNESP]; Forti, Luiz Carlos [UNESP]; Lopes, Juliane Floriano [UNESP]; Andrade, Ana Paula Protti de [UNESP] (Sociedade de Investigações Florestais, 2004)
Ninhos jovens de Acromyrmex subterraneus brunneus caracterizam-se pela terra solta no exterior do ninho, por ter uma única câmara de fungo com profundidade de 11 a 20 cm em relação à superfície do solo e por ter volume interno variando de 0,3 a 1,5 litros. Estes padrões de nidificação são caracteres importantes para a identificação e o conhecimento das interações da espécie com o seu habitat.

Young nests of Acromyrmex subterraneus brunneus are characterized by refuse soil in the exterior of the nest, a single fungus chamber 11 to 20 cm deep in relation to soil surface and internal volume ranging from 0.3 to 1.5 liters. These nidification patterns are important characteristics for identifying and understanding the interactions between species and their habitats.
Caracterização de ninhos jovens de Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) em fragmento de Floresta Neotropical
Keywords: Acromyrmex subterraneus brunneus; formigas cortadeiras; ninho; câmara de fungo; Acromyrmex subterraneus brunneus; leaf-cutting ants; nest; fungus chamber